Dermatofibrosarcoma protuberans: Surgical management of a challenging mesenchymal tumor - Wiesmüller, Felix; Agaimy, Abbas; Perrakis, Aristotelis; Arkudas, Andreas; Horch, Raymund E.; Grützmann, Robert; Vassos, Nikolaos (World Journal of Surgical Oncology, 2019)
Introduction: Dermatofibrosarcoma protuberans (DFSP) is a rare, low-grade malignant mesenchymal tumor of the soft tissue, characterized by slow infiltrative growth and common local recurrence, with rare distant metastases. Patients and methods: We present a retrospective study of nineteen patients who were diagnosed with DFSP and operated at our institution in > 10-year period. We examined the clinicopathological parameters with special emphasis on the margin status regarding the clinical outcome and the follow-up. Results: A total of eight cases underwent re-excision at our institution following primary excision or incisional biopsy performed at a different institution. Seven cases received excision after incisional biopsy at our institution. Four patients developed recurrent disease following primary excision with histological R0 margins at other institutions and received re-excision at our institution. All excisions at our institution resulted in R0 margins with no recurrence recorded at last follow-up (6 to 175; mean 84 months). The mean margin for those who received resection at our institution was 1.67 cm. Negative margins upon primary excision were achieved using a mean margin width of 2.04 cm. Most common tumor localization was the trunk (10 cases). Conclusion: Awareness of this rare entity is important for a prompt diagnosis and a proper management of the disease. The greatest clinical challenge in the management of DFSP is achieving local control. Complete excision of the tumor with surgical margin widths of at least 2 cm is recommended.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Cutaneous lesions; Dermatofibrosarcoma protuberans; DFSP; Mesenchymal tumor; Wallace rule of 9s

Gastrointestinal schwannomas: a rare but important differential diagnosis of mesenchymal tumors of gastrointestinal tract - Mekras, Alexandros; Krenn, Veit; Perrakis, Aristotelis; Croner, Roland S.; Kalles, Vasileios; Atamer, Cem; Grützmann, Robert; Vassos, Nikolaos (BMC Surgery, 2018)
BACKGROUND: Schwannomas of gastrointestinal tract are rare, mostly benign and notably different neoplasms from conventional schwannomas that arise in soft tissue or the central nervous system. These tumors are of clinical importance since they should always be considered in the differential diagnosis of submucosal lesions of gastrointestinal tract. METHODS: Seven patients with a pathologically proven gastrointestinal schwannoma were identified in our series of mesenchymal tumors and reviewed retrospectively. Clinicopathological and immunohistochemical parameters along with the follow-up results were analysed. RESULTS: The series included two males and five females, with a mean age 69 years (range, 39-81). Most patients were asymptomatic on presentation, except for two patients with abdominal pain. In the other cases (n = 5), the tumor was an incidental finding during other medical, imaging or surgical procedures. The tumors were located in the stomach (n = 4) and in the small intestine (n = 3) with an average size of 29 mm (range, 12-70). A preoperative diagnosis was achieved only in one case with a CT-guided core biopsy. Otherwise the clinical, intraoperative, endoscopic or radiological findings were unspecific. Patients with gastric tumor underwent either laparoscopic (n = 2) or open (n = 2) gastric wedge resection of the tumor; in the cases of intestinal tumor (n = 3) a segmentectomy was performed. Pathological examination revealed solid homogenous tumors, which were highly cellular and composed of spindle cells with positive staining for S100 protein, and confirmed the diagnosis of schwannoma. All tumors were negative for c-Kit, smooth muscle actin, desmin and DOG-1 and showed very low proliferation index. There were negative resection margins and no malignant variants were recognized. At an average follow-up of 60 months (range, 24-185) all patients were free of disease with no signs of recurrence or metastases and acceptable gastrointestinal function. CONCLUSIONS: Schwannomas are rare, slow-growing and mostly asymptomatic gastrointestinal mesenchymal tumors. They are difficult to be diagnosed preoperatively as endoscopic and radiological findings are nonspecific but histological and immunohistochemical features are of paramount importance to differentiate between benign and malignant schwannomas, or other spindle cell sarcomas. The treatment of choice is complete surgical excision without a conclusive preoperative diagnosis, and the long-term outcome is excellent as these lesions are mostly benign.
EVALuna2:210708

Incarcerated recurrent inguinal hernia containing an acute appendicitis (Amyand hernia): an extremely rare surgical situation - Velimezis, Georgios; Vassos, Nikolaos; Kapogiannatos, Georgios; Koronakisi, Dimitrios; Perrakis, Evangelos; Perrakis, Aristotelis (Archives of Medical Science, 2017)
EVALuna2:15317

Intra-abdominal localized hyaline-vascular Castleman disease: imaging characteristics and management of a rare condition. - Vassos, Nikolaos; Raptis, Dimitrios; Lell, Michael; Klein, Peter; Perrakis, Aristotelis; Köhler, Jens; Croner, Roland S.; Hohenberger, Werner; Agaimy, Abbas (Archives of Medical Science, 2016)
EVALuna2:6759

Introduction of complete mesocolic excision with central vascular ligation as standardized surgical treatment for colon cancer in Greece. Results of a pilot study and bi-institutional cooperation - Perrakis, Aristotelis; Vassos, Nikolaos; Weber, Klaus; Matzel, Klaus E.; Papadopoulos, Konstantinos; Koukis, Georgios; Perrakis, Evangelos; Croner, Roland S.; Hohenberger, Werner (Archives of Medical Science, 2019)
Introduction: Complete mesocolic excision (CME) is generally accepted as state of the art in colon cancer surgery. However, the long-term impact of CME has not been systematically examined. Therefore cohort studies might be a possible way to clarify any differences between conventional resections and CME. Following bilateral cooperation between the Department of Surgery/University Hospital of Erlangen and the 1st Surgical Department of the General Hospital of Nikaia/Piraeus, including teaching activities for introduction of CME, a cohort study was performed, considering surgical quality criteria and clinical outcome.
CRIS-Team WoS Importer:2019-09-27

Left-sided Gallbladder in the Era of Laparoscopic Cholecystectomy: A Single-center Experience - Velimezis, Georgios; Vassos, Nikolaos; Kapogiannatos, Georgios; Koronakis, Dimitrios; Salpiggidis, Christos; Perrakis, Evangelos; Perrakis, Aristotelis (American Surgeon, 2015)
The malposition of gallbladder under the liver segment III, defined as left-sided gallbladder (LSG), is an unexpected situation for the laparoscopic surgeon. The purpose of this study is to present our experience in treating patients with cholecystitis and LSG discovered incidentally during laparoscopic surgical procedure. Between 1993 and 2009, 5569 patients underwent laparoscopic cholecystectomy in our surgical department. Their records were reviewed and seven patients revealed having LSG (0.12%). Analysis parameters included demographic data, diagnostic methods, mode of surgery, and postoperative outcome. Mean follow-up was 140 months. Of the seven patients, five were women. Mean patient age was 56.7 years. All patients were referred to our department with clinical symptoms of classic cholelithiasis and the diagnosis was established in all of them during surgery. Laparoscopic cholecystectomy was successful in five patients, while in two patients, a conversion to open procedure was needed. A postoperative complication, i.e., biliary leakage was registered in one patient, which was treated successfully. Laparoscopic cholecystectomy is safe even in LSG, but the surgeon must consider the possibility for more anatomical anomalies, adjust the technique of dissection, and must not hesitate, if in doubt, to strive for conversion to open procedure to avoid serious complications.
EVALuna2:15182

Lymph node metastasis of carcinomas of transverse colon including flexures. Consideration of the extramesocolic lymph node stations - Perrakis, Aristotelis; Weber, Klaus; Merkel, Susanne; Matzel, Klaus; Agaimy, Abbas; Gebbert, Carol; Hohenberger, Werner (International Journal of Colorectal Disease, 2014)
Complete mesocolic excision (CME) is nowadays state of the art in the treatment of colon cancer. In cases of carcinoma of transverse colon and of both flexures an extramesocolic lymph node metastasis can be found in the infrapancreatic lymph node region (ILR) and across the gastroepiploic arcade (GLR). These direct metastatic routes were not previously systematically considered. In order to validate our hypothesis of these direct metastatic pathways and to obtain evidence of our approach of including dissection of these areas as part of CME, we initiated a prospective study evaluating these lymph node regions during surgery.Forty-five consecutive patients with primary tumour manifestation in transverse colon and both flexures between May 2010 and January 2013 were prospectively analyzed. Patients were followed up for at least 6 months. Mode of surgery, histopathology, morbidity and mortality were evaluated.Twenty-six patients had a carcinoma of transverse colon, 16 patients one of hepatic flexure and four patients one of splenic flexure. The median lymph node yield was 40. Occurrence of lymph node metastasis in ILR was registered in five patients and in GLR in four patients. The mean lymph node ratio was 0.085. Postoperative complications occurred in nine patients, and postoperative mortality was 2 %.We were able to demonstrate this novel metastatic route of carcinomas of the transverse colon and of both flexures in ILR and GLR. These could be considered as regional lymph node regions and have to be included into surgery for cancer of the transverse colon including both flexures.
EVALuna2:6599

Molecular mechanisms of lymphatic metastasis in solid tumors of the gastrointestinal tract. - Langheinrich, Melanie; Schellerer, Vera; Perrakis, Aristotelis; Lohmüller, Clemens; Schildberg, Claus; Naschberger, Elisabeth; Stürzl, Michael; Hohenberger, Werner; Croner, Roland S. (International Journal of Clinical and Experimental Pathology, 2012)
Tumor cell dissemination from the primary tumor site to distant organs is one of the characteristic properties of malignant tumors and represents a crucial step in the progression of disease. Although the pattern of spread may vary in different types of carcinomas, dissemination via the lymphatic system represents a common event in metastasis. The extent of lymph node metastasis is one of the major determinants for the prognosis of patients with gastrointestinal carcinomas and guides the therapeutically management. During the last decades, significant attention has been given to the molecular mechanisms that control lymphatic metastasis. The process of lymphangiogenesis has come into the focus. Lymphangiogenesis, the formation of newly lymphatics, comprises a series of complex cellular events and is controlled by a balance between pro- and anti-lymphangiogenic signals. This article will briefly describe the lymphatic system and then provide an overview of the molecular players involved in tumor lymphangiogenesis.

Prognostic and diagnostic value of procalcitonin in the post-transplant setting after liver transplantation - Perrakis, Aristotelis; Stirkat, Falk; Croner, Roland S.; Vassos, Nikolaos; Raptis, Dimitrios; Yedibela, Süleyman; Hohenberger, Werner; Mueller, Volker (Archives of Medical Science, 2016)
The aim of the study was to assess the diagnostic accuracy of procalcitonin (PCT) as a marker for complications and as a prognostic factor for mortality after liver transplantation.Liver transplant patients between January 2007 and April 2011 were prospectively included in the study. Procalcitonin serum concentration was recorded before, 6 h after reperfusion and then daily. Postoperative clinical course was prospectively analyzed from admission to discharge. Main surgical data such as operating procedure, type of reperfusion, operating and ischemic times, high urgency (HU) status and MELD score at the time of transplantation were also recorded.Sixteen patients with initial PCT > 5 ng/ml suffered >= 1 complication (p = 0.03). However, there was no association between the level of the 1(st) peak PCT and the further postoperative course or the occurrence of complications. Patients in whom a 2(nd) PCT peak occurred had a significantly higher risk for a complicated course, for a complicated sepsis course and for mortality (p < 0.0001). Warm ischemic time over 58 min, operating time over 389 min and HU status were significant independent factors for a complicated postoperative course (p < 0.001, p < 0.001 and p = 0.03 respectively).Based on our results, we believe that PCT course and the occurrence of a 2(nd) peak seem to possess important diagnostic and prognostic power in the post-transplant setting after liver transplantation.
EVALuna2:15234

Qualität der Chirurgie als Prognosefaktor beim Rektumkarzinom nach neoadjuvanter Radiochemotherapie - Brunner, M.; Perrakis, Aristotelis; Merkel, Susanne; Weber, K.; Grützmann, Robert (Chirurgische Praxis, 2019)
The prognosis of patients with rectal carcinoma has improved significantly in recent years, in particular through the introduction of TME (total mesorectal excision) surgery and neoadjuvant therapy with radiation or chemoradiotherapy in locally advanced carcinomas. Even in the era of TME surgery and neoadjuvant chemoradiation high-quality surgical therapy plays an important role for the prognosis of patients with rectal cancer, especially for local tumor control. Prognostically relevant surgical quality indicators represent the quality of TME, the R0 resection, the negative circumferential resection margin (CRM) and the avoidance of intraoperative local tumor cell dissemination. These four factors mainly affect the local recurrence rate, but are also significant in terms of overall survival.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Neoadjuvant therapy; Preoperative chemoradiation; Prognostic factors; Quality of surgery; Rectal carcinoma; TME

Quality of Surgery for Stage III Colon Cancer: Comparison Between England, Germany, and Japan - Kobayashi, Hirotoshi; West, Nicholas P.; Takahashi, Keiichi; Perrakis, Aristotelis; Weber, Klaus; Hohenberger, Werner; Quirke, Philip; Sugihara, Kenichi (Annals of Surgical Oncology, 2014)
A number of studies have demonstrated that lymph node metastasis is a poor prognostic factor in colon cancer. Advances of surgical procedure have improved the outcomes of colon cancer treatment. The aim of this study was to compare the characteristics of surgery for stage III colon cancer between England, Germany, and Japan.Using the data of patients with colon cancer from one English, one German, and two Japanese centers, the characteristics of clinicopathologic features were compared. Conventional surgery, complete mesocolic excision (CME) with central vascular ligation, and D3 lymph node dissection were performed in England, Germany, and Japan, respectively.Nineteen English, 26 German, and 60 Japanese patients were enrolled. There was no difference in tumor location, pT, and pN factors among the three groups. The length of resected bowel and the area of resected mesentery of the English and CME specimens were significantly greater than those of the D3 specimens (P < 0.0001 and P < 0.0001, respectively), whereas the length of the vascular tie to the bowel wall was similar between the CME and D3 specimens (P = 0.87), which was longer than that of the English specimens. The number of lymph nodes retrieved in the CME specimens was greatest among three groups (P < 0.0001), although the number of positive nodes was comparable (P = 0.64). The rates of mesocolic plane surgery in the English, CME, and D3 specimens were 47.4, 88.5, and 71.7 %, respectively (P = 0.022).Three types of surgery for colon cancer differed in terms of the length of the resected bowel and the area of mesentery, although the length of the vascular tie to the bowel wall was similar between CME and D3 specimens. The high rates of mesocolic plane surgery were demonstrated in the CME and D3 specimens.
EVALuna2:15164

Results of Surgical Treatment of Hiatal Hernia. - Schildberg, C. W.; Perrakis, Aristotelis; Croner, R.; Schellerer, Vera; Haupt, Werner; Weidinger, T.; Hohenberger, Werner; Horbach, T. (Zentralblatt für Chirurgie, 2014)
Background: Hiatus hernias are considered as the most prominent form of diaphragmatic hernias. The passage is defined through the oesophageal hiatus, resulting in a superdiaphragmatic displacement of parts of the stomach or the complete stomach, respectively. In our work we investigated the treatment of partial thoracic stomach with both open and minimally invasive surgical procedures emphasising the view on operating data, the success of the surgery and recurrence rates. Patients with mesh insertion for hernia defect closures were considered separately.Material and Method: 94 Patients were treated in the period from 01.01.2003 to 01.06.2010. The ratio male/female was 2 : 1. The median age was 66 years. All data were prospectively collected by means of surgical protocols and data from the central patient records and analysed retrospectively. The statistical analyses were performed with SPSS 18.0 (SPSS Inc., Chicago, IL, USA). Any existing significances were determined using the T-test.Results: Of the 94 patients, 65 were operated laparoscopically. In the case of nine patients an initial laparoscopic surgery had to be changed to an open procedure. The reasons for switching surgical procedures were splenic bleeding in the case of 2 patients, intestinal injury due to perforation by the trocar in one case and unclear surgical situs in 6 cases. The postoperative complication rate was 24 %. The main reasons were a delayed achievement of passage. The mortality rate was 0 %. The comparison between laparoscopic and open groups showed, by comparable complication and recurrence rates, a shorter recovery time in favour of patients operated on laparoscopically. Additionally it can be stated that a bridge closure with mesh (ePTFE) had no significant influence on the postoperative outcome. Therefore we cannot confirm the postulated poor postoperative results of other groups. Conclusion: In summary, the clear trend in the surgical treatment of hiatus hernias is to minimally invasive surgery. Only for patients with multiple previous operations, who are expected to have strong adhesions, the operation with comparable morbidity and mortality rates can also be planned primarily as open. In this case, however, longer postoperative recovery times must be expected. Large defects can be treated with comparable complication and recurrence rates by mesh insertion (ePTFE).
EVALuna2:15112

Robotic-Assisted Liver Surgery - Croner, R.; Perrakis, Aristotelis; Grützmann, Robert; Hohenberger, Werner; Brunner, Michaela (Zentralblatt für Chirurgie, 2016)
The advantages of minimally invasive liver resections for selected patients are evident. Robots provide new innovations that will influence minimally invasive liver surgery in the future. This article presents our initial experience with this technology in our patient population. Material und Methods: In 14 patients with benign or malignant liver tumours, robotic-assisted liver surgery was performed. Selection criteria were compensated liver function and resection of <= 3 liver segments. Chronic liver disease or previous abdominal surgery were no exclusion criteria.Malignant liver tumours were removed in 10 patients (71 %) and benign symptomatic liver tumors in 3 patients (21 %), respectively, with histopathologically negative margins (R0). One patient suffering from HCC underwent intraoperative ablation. In one case (7 %) conversion was necessary. Mean operation time was 296 min (120-458 min); mean estimated blood loss was 319 ± 298 ml. The mean hospital stay of the patients was 8 days (3-17 days). Three patients (21 %) suffered from postoperative complications, which were manageable by conservative treatment (Clavien-Dindo I) in 2 cases (14 %). One patient (7 %) needed endoscopic treatment for postoperative bile leak (Clavien-Dindo III a). No patient died intra- or perioperatively.Robotic-assisted liver surgery is a safe procedure, which provides patients with all benefits of minimally invasive surgery. This highly advanced technology requires surgeons to strive for an increasing level of specialisation, in addition to being well-trained in liver surgery. Hence, a clear definition of the procedures and standardised teaching programs are necessary.
EVALuna2:15228

Robotic liver surgery for minor hepatic resections: a comparison with laparoscopic and open standard procedures - Croner, Roland S.; Perrakis, Aristotelis; Hohenberger, Werner; Brunner, Michaela (Langenbecks Archives of Surgery, 2016)
Minimally invasive liver surgery is increasing worldwide. The benefit of the robot in this scenario is currently controversially discussed. We compared our robotic cases vs. laparoscopic and open minor hepatic resections and share the experience.From 2011 to 2015, ten patients underwent robotic and 19 patients underwent laparoscopic minor liver resections in the Department of Surgery, University Hospital Erlangen. These patients were compared to a case-matched control group of 53 patients. The perioperative prospectively collected data were analyzed retrospectively.Blood loss was significantly decreased in the robotic (306 ml) and laparoscopic (356 ml) vs. the open (903 ml) surgery group (p = 0.001). Mean tumor size was 4.1-4.8 cm in all groups (p = 0.571). Negative surgical margins were present in 94 % of the open and 100 % of the laparoscopic and robotic group (p = 0.882). Time for surgery was enlarged for robotic (321 min) vs. laparoscopic (242 min) and open (186 min) surgery (p = 0.001). Postoperative hospitalization was decreased after robotic (7 days) and laparoscopic (8 days) vs. open (10 days) surgery (p = 0.004). Total morbidity was 17 % for open, 16 % for laparoscopic, and 1 % for robotic cases (p = 0.345). Postoperative pain medication and elevation of liver enzymes were remarkably lower after minimally invasive vs. open procedures.Minimally invasive liver surgery can be performed safely for minor hepatic resections and should be considered whenever possible. Minor liver resections can be performed by standard laparoscopy equivalent to robotic procedures. Nevertheless, the robot adds a technical upgrade which may have benefits for challenging cases and major liver surgery.
EVALuna2:15231

Strangulation and necrosis of right hemicolon as an extremely rare complication of Spigelian hernia - Velimezis, Georgios; Vassos, Nikolaos; Kapogiannatos, Georgios; Koronakis, Dimitrios; Salpiggidis, Christos; Perrakis, Evangelos; Perrakis, Aristotelis (Archives of Medical Science, 2016)
EVALuna2:15264

Surgery along the embryological planes for colon cancer: a systematic review of complete mesocolic excision - Gouvas, Nikolaos; Agalianos, Christos; Papaparaskeva, Kleio; Perrakis, Aristotelis; Hohenberger, Werner; Xynos, Evaghelos (International Journal of Colorectal Disease, 2016)
Complete mesocolic excision (CME) for colonic cancer offers a surgical specimen of higher quality, with higher number of lymph nodes compared to conventional colectomy. However, evidence on oncological outcomes is limited. The aim of the present study is to review recent literature and provide more information regarding the effect of CME colectomy on short- and long-term outcomes.PubMed and MEDLINE databases were searched, and articles in English reporting data on CME were reviewed. Intraoperative events; postoperative morbidity and mortality; histopathological characteristics, including macroscopic assessment, number, and status of retrieved lymph nodes; and oncological outcomes were the end-points.Thirty-two studies were analyzed. As regards the macroscopic assessment, a larger specimen (p = 0.02) that contains a higher number of lymph nodes (p < 0.00001) is acquired after CME. Two studies report a higher disease-free survival, in stage I and II and particularly in stage III disease after CME. CME by laparoscopy offers comparable outcomes, as regards intraoperative blood loss and immediate postoperative morbidity and mortality rates. Specimen quality is similar after either approach, for cancers located at the right and left colon, but not at the transverse colon.There is strong evidence that CME offers a longer central pedicle that contains more lymph nodes than conventional surgery for colon cancer. CME represents the surgical background for the maximum lymph node harvest, an important quality marker for the surgical outcome. However, and according to present data, there is limited evidence that colectomy in terms of CME leads to improved long-term oncological outcomes.
EVALuna2:15245

Surgery for metastases, anatomical and ethical limits : Special aspect: oligometastases - Perrakis, Aristotelis; Juratli, T. A.; Hohenberger, Werner; Croner, R. S.; Schackert, G. (Chirurg, 2016)
The surgical resection of metastases is nowadays feasible in selected patients with multifocal metastatic disease due to the implementation of interdisciplinary multimodal therapeutic options. Anatomical limitations do not seem to represent obstacles which cannot be overcome because of the development of new surgical techniques. The cornerstone of the selection of patients is the correct staging diagnosis achieved through modern diagnostic tools; however, surgery alone does not always offer acceptable survival and recurrence-free rates. Furthermore, in every complex surgical procedure there is the risk of morbidity and mortality; therefore, parameters such as alternative therapeutic modalities, the individual situation of the patient and tumor biology have to be considered in order to make the correct selection of patients. This is one of the major future challenges and should never be driven by unfounded hopes and expectations of the patients. The same principle also applies for brain metastases, which represent the most common brain tumors. Approximately 70 % of patients with brain metastases have 1-3 lesions (oligometastases). Treatment is now individualized and the goal of therapy has shifted towards long-term survival (>= 24 months) and improved quality of life. Under this aspect surgery is one of the important treatment options, particularly in patients with a single metastasis or oligometastases. Furthermore, approximately 20 % of patients who have recurrent brain metastases, successfully undergo a complete resection of tumors and with a Karnofsky performance status (KPS) score > 70 show a long-term survival of >= 24 months.
EVALuna2:15224

What is Changing in Indications and Treatment of Focal Nodular Hyperplasia of the Liver. Is There Any Place for Surgery? - Perrakis, Aristotelis; Vassos, Nikolaos; Grützmann, Robert; Croner, Roland S. (Annals of Hepatology, 2017)
Focal nodular hyperplasia (FNH) is a common benign liver tumor, which occurs in the vast majority of the cases in young women. FNH represents a polyclonal lesion characterized by local vascular abnormalities and is a truly benign lesion without any potential for malignant transformation. A retrospective single institution analysis of 227 FNH patients, treated from 1990 to 2016 and a review of studies reporting surgical therapy of overall 293 patients with FNH was performed. Indications for resection with a focus on diagnostic workup, patient selection, surgical mode and operative mortality and morbidity have been analysed. Ninety three patients underwent elective hepatectomy and 134 patients observation alone, where median follow-up was 107 months. Postoperative complications were recorded in 14 patients, 92% of patients reported an improvement with respect to their symptoms. Overall among 293 patients underwent surgery in the series, included to this review, there was a morbidity of 13%, where median follow-up was 53 months. Systematic follow-up remains the gold standard in asymptomatic patients with FNH. However elective surgery should be considered in symptomatic patients, in those with marked enlargement and in case of uncertainty of diagnosis. Surgery for FNH is a safe procedure with low morbidity and very good long term results as far as quality of life after surgery is concerned and surely an integral part of the modern management of FNH.
EVALuna2:15281